Analisis Gaya Kognitif Siswa Pada Pengajuan Masalah - Luthfiana, Nadya Afifah; Kurniawan, Riza Yonisa (Universitas Negeri Surabaya, 2024)
This research is used to describe the cognitive style of students in problem posing. The purpose of this research is to find out which cognitive style is superior in problem posing. The study uses the Systematic Literature Review (SLR) method with the aim of drawing conclusions from the results of students' cognitive style research when making questions on problem posing. This study consists of 15 articles regarding cognitive styles which will be grouped by type. Selection of the article through Google Scholar. The results are that each cognitive style has subjects that are superior in terms of posing problems compared to the other, such as field independent cognitive style is superior to field dependent cognitive style, reflective cognitive style is superior to impulsive cognitive style, and verbalizer cognitive style is superior of the cognitive visualizer style.